In vitro study of antiamoebic effect of methanol extract of mature seeds of Carica papaya on trophozoites of Entamoeba histolytica (Bangladesh Journal of Pharmacology, 2010)
Antiamoebic activity of methanol extract of mature seeds of Carica papaya was tested in vitro on axenic culture of Entamoeba histolytica using metronidazole as a reference amoebicidal agent. The MIC of seed extract was >62.5 µg/mL as compared to